STRATEGI KOMUNIKASI ORANG TUA DALAM MEMBANGUN KETERBUKAAN EMOSIONAL ANAK: ANALISIS KONTEN SKENARIO KELUARGA KIMBAB FAMILY DI YOUTUBE - Siti Komala Mutiara; Ferica Innestesya; Anjas Aditya Hartono; Muhammad Armahadi Rahmawan; Malik Ibrahim (Nusantara Hasana Journal, 2026)
This study aims to analyze the verbal and non-verbal communication strategies used by Mama Gina and Appa Jay on the Kimbab Family YouTube channel, as well as to evaluate their alignment with the characteristics of authoritative parenting according to Diana Baumrind's theory. Using a descriptive qualitative approach, this study applies Klaus Krippendorff's qualitative content analysis method with an inductive category approach. The units of analysis include conversation transcripts and visual gestures from six main videos containing one-on-one deep talk interaction scenarios between the parents and their three children: Suji, Yunji, and Jio. The results indicate that verbal communication strategies are implemented through opinion stimulation, validation of negative emotions, and evaluation of sibling dynamics. These are reinforced by non-verbal cues such as eye-level contact, active listening, spatial proximity, and tactile touch (hugs and hand-holding) which effectively foster children's psychological safety. Theoretically, Mama Gina and Appa Jay's interpersonal communication practices highly align with Baumrind's authoritative parenting model, which successfully balances rational control and emotional responsiveness while respecting children's autonomy of thought in the digital space.